Pengaruh Lapisan Karbon Pada Cetakan Permanen Terhadap Distribusi Kekerasan Grinding Cyl Dengan Material Besi Cor Kelabu - Assrofi, Husen Muhammad; , Agus Yulianto, ST, MT (2017)
The research aims to determine the effect of the carbon coating on the solidification of gray cast iron in a permanent mold for the initial tapping. This research uses a permanent mold cast iron ductile (FCD). This research methodology was conducted with cast iron melting in induction furnace and the is poured in the mold FCD coated carbon to create gray cast iron specimens were then tested the physical properties and mechanical. The testing in the form of liquid grey cast iron CE Meter test equipment spectrometer then in the micro hardness tester and photos are taken from the direct contact with the air and direct contact the mold FCD. The result of the research is a chart obtained from CE Meter indicates the temperature 1260.3°C during tapping intial cast in the mold begins on the chart that reads CE Meter decrease temperature of solid 1118.7°C so that the value CEL= 4,47% ; C= 3,98% and SI= 1,86% where in iron solid starts but still the red until 1060°C temperature and hardened whitin 180 seconds, while the result of chemical composition in the form of solid or solid among others : Fe 93,26% ; C 3,06% ; Si 1,80% and other elements below 1%. Test result microstructure in the section of the specimen hardness test looks graphite and cementite and hardness test result A=82.54, 90.15, 91.27, 87.60, 86.09. B=86.60, 90.44, 90.03, 88.77, 88.60. C=92.07, 96.20, 96.66, 88.38, 90.83. and D= 96.12, 92.85, 92.28, 93.81, 94.50 and specimens at the highest hardness rate in the C3 at 96.66 , while the price of the A1 82.54 based on this data we can conclude that each part has a varied level of hardness, because each point or section in the test has a carbon content of different the higher the carbon content. The higher the level of hardness and influence the nature of fission gray cast iron. Keyword : solidification, molding FCD, spectrometer, microstructure, hardness.